(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Preschool of age to children English language teaching modern education system important is part of and this of the process to oneself typical features children’s psychological and cognitive to develop suitable accordingly is formed. This in research preschool of age to children English language of teaching main Features – playful methods, songs, visuals tools and immersion (full) language to the environment immersion) through studied. Research the purpose of this of methods efficiency assessment and children’s language skills in development their the impact determination. With the participation of 60 children aged 5-6 held experience results this showed that the game and interactive methods children’s word wealth by 28%, pronunciation by and by 35% . The results are consistent with Piaget and Vygotsky theories based on discussion made education​​ in the process children’s natural interest into account to take the necessity emphasizes. The research practical importance – educators for new methods offer is to reach.